Cancer Metabolism: The Role of ROS in DNA Damage and Induction of Apoptosis in Cancer Cells - Zhao, Yongxia; Ye, Xiaochun; Xiong, Zhifeng; Ihsan, Awais; Ares, Irma; Martínez, Marta; Lopez-Torres, Bernardo; Martínez-Larrañaga, María-Rosa; Anadón, Arturo; Wang, Xu; Martínez, María-Aránzazu (Metabolites, 2023)
Cancer is a huge challenge for people worldwide. High reactive oxygen species (ROS) levels are a recognized hallmark of cancer and an important aspect of cancer treatment research. Abnormally elevated ROS levels are often attributable to alterations in cellular metabolic activities and increased oxidative stress, which affects both the development and maintenance of cancer. Moderately high levels of ROS are beneficial to maintain tumor cell genesis and development, while toxic levels of ROS have been shown to be an important force in destroying cancer cells. ROS has become an important anticancer target based on the proapoptotic effect of toxic levels of ROS. Therefore, this review summarizes the role of increased ROS in DNA damage and the apoptosis of cancer cells caused by changes in cancer cell metabolism, as well as various anticancer therapies targeting ROS generation, in order to provide references for cancer therapies based on ROS generation.